2019
DOI: 10.1111/jog.14134
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal versus transvaginal specimen extraction in mini‐laparoscopic surgery

Abstract: Aim: The objective of this study was to present our experiences of tissue extraction via the transvaginal (TV) route after a mini-laparoscopic gynecological surgery and compare them with our transabdominal (TA) specimen extraction experiences. Methods: This prospective randomized controlled study was conducted in a tertiary care center between July 2014 and February 2016. Fifty-eight women who were undergoing mini-laparoscopy for adnexal mass removal were randomized into two groups according to the surgical sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…When performing multiport laparoscopic surgery for large organs such as the stomach, colon, kidney, liver, and spleen, the extraction of surgical specimens requires an additional or enlarged abdominal wall incision to remove the resected organ or tissue. Enlargement of the incision may cause abdominal pain, infection, and incisional hernia during the postoperative period [ 2 ]. Natural orifice specimen extraction (NOSE) has been suggested to reduce incision-related morbidity and maximize the advantages of laparoscopic surgery [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When performing multiport laparoscopic surgery for large organs such as the stomach, colon, kidney, liver, and spleen, the extraction of surgical specimens requires an additional or enlarged abdominal wall incision to remove the resected organ or tissue. Enlargement of the incision may cause abdominal pain, infection, and incisional hernia during the postoperative period [ 2 ]. Natural orifice specimen extraction (NOSE) has been suggested to reduce incision-related morbidity and maximize the advantages of laparoscopic surgery [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among various developed NOSE techniques, gynecologists have most widely selected the transvaginal access route through a posterior colpotomy incision [ 2 , 3 ]. The posterior vaginal fornix is a large recess behind the cervix, a relatively accessible part of the vagina, and has good healing ability due to adequate vascular supply [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enlargement of the abdominal wall incision can lead to postoperative complications, including postoperative pain, surgical site infections, incisional hernias, and cosmetic problems (2,3). NOSE can address these problems when surgeons incorporate it into existing minimally invasive surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…When performing multiport laparoscopic surgery for large organs such as the stomach, colon, kidney, liver, and spleen, the extraction of surgical specimens requires an additional or enlarged abdominal wall incision to remove the resected organ or tissue. Enlargement of the incision may cause abdominal pain, infection, and incisional hernia during the postoperative period (2). Natural ori ce specimen extraction (NOSE) has been suggested to reduce incision-related morbidity and maximize the advantages of laparoscopic surgery (1).…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the self-made device lacks a fixed point or fulcrum. Numerous studies have suggested that using posterior colpotomy to extract surgical specimens during laparoscopy or to perform an endoscopic operation has no negative effects on female sexual function [31][32][33]. In addition, Uccella et al showed that using the vagina for mass extraction allows the introduction of larger endobags without increasing the width of the incision on the abdomen during laparoscopic surgery [34].…”
Section: Discussionmentioning
confidence: 99%